Civil Islam Movement is Responding to Environmental Degree Yogyakarta City (Study: Environmental Council For Muhammadiyah Regilonal Leadership in Yogyakarta - Ruli Desianti; David Efendi; Alam Mahadika (FKIP, Universitas Palangka Raya, 2022)
The purpose of this study is to examine the ideology that underlies the birth and development of the Muhammadiyah environmental movement and its relationship with the MLH PDM Yogyakarta City, strategies for achieving the movement's goals, and its contribution to improving the environmental quality of Yogyakarta City. This research was conducted using a qualitative case study method with primary and secondary data obtained from interviews, documentation, and observation. Meanwhile, the concepts used to analyze the data are Herbert Blumer's Symbolic Interactionism theory, the environmental movement and the Ecological Ethics of Islamic Pantheism, and civil society. The results showed that the environmental movement by MLH PDM Yogyakarta City was related to the MLH PPM movement or the Muhammadiyah environmental movement in general as a representation of Islamic-based civil society. In particular, the environmental movement MLH PDM Yogyakarta City is assessed from the commitment of its members in implementing the program from MLH PPM and the efforts taken to optimize program implementation through; (1) transfer of knowledge about environmental issues to external parties, (2) framing environmental issues through journalism activities, (3) innovation in the Shodaqoh Waste program, (4) collaboration with internal and external Muhammadiyah institutions, (5) holding periodic forums in the form of internal meetings, and (6) make plans to implement the Rainwater Harvesting movement in the PDM environment of Yogyakarta City. Meanwhile, in general, the Muhammadiyah environmental movement contributes to the improvement of the environment and economic, socio-cultural, and political aspects, especially in public policy